Content Analysis Of Entrepreneurship Semester Learning Plan (RPS) Versus Character Education And Professional Ethics In The Heavy Equipment Engineering Study Program Of Padang State Polytechnic - Rusmardi Rusmardi (Journal Of Social Science (JoSS), 2023)
The study aims to compare the content of the Semester Learning Plan (RPS) of the Entrepreneurship and Character Education and Professional Ethics courses in the Heavy Equipment Study Program of the Padang State Polytechnic. This research is qualitative and based on the concept of "logic-hypothetic-verification". The analysis was carried out based on theoretical studies and content analysis of the two RPS and obtained a correlation between the two. The results of the study found that there is a strong relationship between RPS Entrepreneurship and RPS Character Education and Professional Ethics. Based on research, it is recommended that the two courses can be combined so that they become one new course under the name Entrepreneurship Character Education so that the learning objectives do not overlap so that the educational process is more economical so that the implementation of learning activities is more effective and efficient.